If you mean the question 3p=0.064 then to find the answer you divide 0.064 by 3 to get 0.213333.....
Step-by-step explanation:
Sum of arithmetic terms = n/2 × [2a + (n - 1)×d], where 'a' is the first term, 'd' is the common difference between two numbers, and 'n' is the number of terms.
this is the same as n/2 × (a1 + an), because
an = a1 + (n-1)×d
so, for the series above :
a or a1 = 2
d = 7, as every new term is the previous term plus 7.
for n
37 = a1 + (n-1)×d = 2 + (n-1)×7
and now solve for n
35 = 7n - 7
42 = 7n
n = 6
so, the sum of all terms is
6/2 × (2+37) = 3×39 = 117
Answer:
1 is the answer to your question mate